No differences in grades or level of satisfaction in a flipped classroom for neuroanatomy - Whillier, Stephney (J Chiropr Educ, 2015)
OBJECTIVE: The intensive nature of a 5- or 6-week teaching block poses unique problems for adequate delivery of content. This study was designed to compare the delivery of a unit of undergraduate neuroanatomy in a short summer school period, as a traditionally taught unit, with a rendition given in the form of the “Flipped Classroom.” The aim was to evaluate the effectiveness of the flipped classroom in the intensive mode classroom. METHODS: The flipped classroom encompassed the same learning outcomes, but students were responsible for covering the content at home in preparation for tutorials that applied their acquired knowledge to higher levels of thinking. The main outcome measures were the final course grades and the level of satisfaction with the course. RESULTS: There were no significant differences between the 2 cohorts in final grades (p = .259), self-rated knowledge (p = .182), or overall satisfaction with the course (p = .892). CONCLUSION: This particular design of the flipped classroom did not add value to the intensive mode experience. It may be that this mode of delivery is ill suited to intensive classes for subjects that carry a lot of content. The use of the flipped classroom requires further research to fully evaluate its value.